INTERACTION OF PROCAINE WITH KEY PROTEINS FOR HEART DEVELOPMENT IN ZEBRAFISH: IN SILICO ANALYSIS - Mitović, Nikola; Milošević, Milica; Ristic, Masa; Dimitrijević, Ljubica; Kovačević, Sanjin; Nešović Ostojić, Jelena; Stankovic, Marija (HEALTH CARE, 2024)
Introduction/Aim: Procaine is a local anesthetic from the amino ester group that blocks voltage-gated sodium channels. Since it can cross the placenta in its ionized form, its potential impact on embryonic development is of concern. Zebrafish, which have a significant degree of homology with the human genome, allow for the study of cardiovascular system development with reliable extrapolation to humans. Investigation of the effects of procaine on key proteins involved in zebrafish heart development using molecular docking. Methods: First, a screening of the interaction between procaine and the entire human proteome was performed using FINDSITEcomb software. Based on significant interactions with a high degree of analysis precision, 113 proteins were selected. Using the ZFIN database, the degree of homology between the selected human proteins and zebrafish proteins, tissue specificity, and expression timing were determined. Nine proteins met all the criteria: kcnh6a, kcnh7, kcnh5a, kcnh2a, psen2, rbfa, and zfpl1, and were further investigated through molecular docking in the AutoDock Vina program. Results: Most of the proteins were highly expressed during the blastula stage. Docking results showed that the scn1laa protein and procaine had the lowest Gibbs free energy value (-6 kCal/mol), while the zfp11 protein had the highest value (-4.4 kCal/mol). Procaine binding to the tested proteins revealed similar amino acid sequences within the same protein family. Conclusion: Procaine interacts with proteins involved in zebrafish heart development under in silico conditions. Further analyses on live embryos are needed to complement these findings.
Keywords: procaine, heart development, zebrafish, molecular docking